Preclinical evaluation of the epithelial sodium channel inhibitor BI 1265162 for treatment of cystic fibrosis. Issue 4 (7th December 2020) - Nickolaus, Peter; Jung, Birgit; Sabater, Juan; Constant, Samuel; Gupta, Abhya
Background: Epithelial sodium channel (ENaC) is an important regulator of airway surface liquid volume; ENaC is hyperactivated in cystic fibrosis (CF). ENaC inhibition is a potential therapeutic target for CF. Here, we report in vitro and in vivo results for BI 1265162, an inhaled ENaC inhibitor currently in Phase II clinical development, administered via the Respimat® Soft Mist™ inhaler. Methods: In vitro inhibition of sodium ion (Na + ) transport by BI 1265162 was tested in mouse renal collecting duct cells (M1) and human bronchial epithelial cells (NCI-H441); inhibition of water transport was measured using M1 cells. In vivo inhibition of liquid absorption from rat airway epithelium and acceleration of mucociliary clearance (MCC) in sheep lungs were assessed. Fully differentiated normal and CF human epithelium was used to measure the effect of BI 1265162 with or without ivacaftor and lumacaftor on water transport and MCC. Results: BI 1265162 dose-dependently inhibited Na + transport and decreased water resorption in cell line models. BI 1265162 reduced liquid absorption in rat lungs and increased MCC in sheep. No effects on renal function were seen in the animal models. BI 1265162 alone and in combination with CF transmembrane conductance regulator (CFTR) modulators decreased water transport and increased MCC in both normal and CF airway human epithelial models and also increased the effects of CFTR modulators in CF epithelium to reach the effect size seen in healthy epithelium with ivacaftor/lumacaftor alone. Conclusion: These results demonstrate the potential of BI 1265162 as a mutation agnostic, ENaC-inhibitor-based therapy for CF. ENaC inhibition is a potential strategy for a mutation-agnostic therapy in CF. In preclinical studies, BI 1265162 is a potent ENaC inhibitor, alone and in synergy with CFTR modulators, supporting Phase I clinical development. https://bit.ly/3mCeWE9